Evaluation of methanolic extract of Phragmites karka on carbon tetrachloride-induced liver fibrosis in rat - Atta ur Rehman; Manal Liaqat; Rabia Asghar; Nawazish-i-Husain Syed (Bangladesh Journal of Pharmacology, 2017)
Phragmites karka has been reported for its anti-inflammatory and analgesic activities. Here, extracts of leaf and rhizome of the plant were individually investigated in CCl4-induced hepatofibrosis in male Wistar rats by administering CCl4 intraperitoneally biweekly for 6 weeks.  Afterwards the animals were investigated for liver fibrosis at biochemical, molecular and histological levels, and it showed a profound increase (p<0.001) in elevation of serum levels of transaminases, ?-glutamyl transpeptidase, mRNA expression of ? smooth muscle actin, collagen and transforming growth factor beta (TGF?), and extracellular matrix deposition and perilobular necrosis. Both extracts markedly (p<0.001) decreased the elevated levels of these markers. Histopathological investigations also substantiated the above results by exhibiting a decreased in extracellular matrix deposition in post-treatment animals. In conclusion, both extracts had substantially modified the biochemical and molecular markers of liver fibrosis, in addition to histological improvement in architecture of liver. Video Clip of Methodology: Expression evaluation of gene: 4 min 43 sec   Full Screen   Alternate